PERAN ORANG TUA DALAM MENGHADAPI PEMBELAJARAN TATAP MUKA - Ahmad Fachrurrazi; Made Ayu Anggreni (Bajang Institute, 2022)
The length of time (period) of learning from home (BDR) during the COVID-19 pandemic has more or less an effect on the readiness of children to learn face-to-face. Maybe children still feel reluctance to learn face to face at school because they are used to learning conditions at home while lying down, playing gadgets and so on. The role of parents is needed to motivate children to want to learn face-to-face at school again. In connection with this, the Community Service Team of the PG-PAUD Study Program, Universitas PGRI Adi Buana Surabaya held a socialization about the role of parents in dealing with face-to-face learning. This program aims to provide motivation and reinforcement to parents of students so that they can help and motivate children in facing face-to-face learning (PTM) at school. The target of this program is the parents of TK LIYA III Surabaya. The method applied is counseling in the form of socializing the role of parents in facing face-to-face learning at school